Yoga para niños: mediación que minimiza la violencia escolar - Páez Martínez, Nidya Soraya (Educación y Ciudad, 2016)
Yoga at school as pedagogical mediation helps to reduce school violence. This conclusión is derived from the pedagogical experience “Yoga, education and life” which was conducted between 2008 and 2012 in the Colegio Técnico Distrital República de Guatemala in Bogotá and the research entitled “Interaction without violence”. In both cases it was concluded that to enhance the interaction without violence in schools, the use of a pedagogical devices in the classroom that enhance not only the externality but also the interiority of children, such as yoga, useful for teacher which shares a long time with them.